2017
DOI: 10.1111/cen.13481
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low‐dose human chorionic gonadotropin combined with human menopausal gonadotropin protocol on women with hypogonadotropic hypogonadism undergoing ovarian stimulation for in vitro fertilization

Abstract: Low-dose hCG combined with HMG is a feasible protocol for HH women undergoing ovarian stimulation in IVF, providing favourable cycle characteristics and pregnancy rates. Low-dose hCG reduces HMG duration, whilst the hCG dose and embryo quality are not positively correlated. The outcomes of FET are comparable to ET, which provides a greater chance of success from IVF in the low responders with HH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Our results suggested that the addition of 150 IU of hCG in early follicle phase could provide a better clinical outcome compared with that in mid-late phase addition. Our results were in line with previous studies that the addition of LH/hCG could increase oocyte number and E 2 production (15,16). A meta-analysis confirmed that the use of rLH/hCG increased the peak E 2 levels and oocyte number and improved embryo quality and, therefore, enhanced implantation rate (17).…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggested that the addition of 150 IU of hCG in early follicle phase could provide a better clinical outcome compared with that in mid-late phase addition. Our results were in line with previous studies that the addition of LH/hCG could increase oocyte number and E 2 production (15,16). A meta-analysis confirmed that the use of rLH/hCG increased the peak E 2 levels and oocyte number and improved embryo quality and, therefore, enhanced implantation rate (17).…”
Section: Discussionsupporting
confidence: 92%
“…COS protocols for assisted reproduction in women with HH are described in Table 3. The reported pregnancy rates after COS amongst HH women vary wildly, from 19.4 to 100%, with a 3.6-41.7% risk of multiple pregnancies [88][89][90][95][96][97][98][99][100]. Higher gonadotropin doses are generally used than in patients with other causes of infertility [101].…”
Section: Female Infertilitymentioning
confidence: 99%
“…Another study with HH patients due to multiple etiologies also reported lower AFC [2]. However, many authors reported normal follicular count, but these results could be explained by the type of patients in the studies where women with small-sized ovaries who showed multi follicular or normal-sized ovaries as in cases of functional hypogonadism were included [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadotrophic hypogonadism (HH) diagnosis was based on clinical history of primary or secondary amenorrhea, negative progestin challenge, serum levels of both FSH and luteinizing hormone (LH) < 5 IU/L, accompanied by serum estradiol levels below 20 pg/mL [2].…”
Section: Introductionmentioning
confidence: 99%